BIONICS IN PLANNING OF HABILITATION FOR CHILDREN WITH CEREBRAL PALSY: BIONICS IN PLANNING OF HABILITATION FOR CHILDREN WITH CEREBRAL PALSY - Dukendjiev, Evgeni (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Assessment of integral deficit of muscular and controlling activity (which needs to be compensated by external energy and information) comes down to defining the difference between biomechanical and neurological activity in health and in disease by com-paring a set of parameters of chronological age in health with the actual child's chronality parameters. The difference between these values creates the aggregate amount of deficit (Î”) followed by the amount of free time (D) and the amount of external energy (Ð•) necessary for habilitation.